PENGARUH PEMBERIAN PAKAN PENGISI PADA AYAM BROILER UMUR 22-28 HARI TERHADAP PERTUMBUHAN, DAN KANDUNGAN LEMAK KARKAS DAN DAGING - Tri Rumiyani; Wihandoyo (Wihandoyo); Jafendi Hasoloan Purba Sidadolog (Buletin Peternakan, 2011)
The experiment was conducted to study the effect of stuff feeding given during 22 to 28 days of ages on growth, meat fat and abdominal fat of broiler. Ninety broiler males (J) and 90 broiler females (B) were divided into 6 treatments groups with 3 replications of 10 broiler chickens each. The treatment were control (K) chicken which was fed with commercial diets from DOC to 42 days of age, DJ and P chickens were fed with corn bran (DJ) or pollard (P) from 22 to 28 days and continued with commercial feeding until 42 days. Feeds for DJ and P treatment was supplemented with B-12 mineral. Data collected were body weight, feed consumption, feed conversion, carcass weight, meat as well as abdominal fat. The data were analyzed by analysis split-plot design (3 feed treatments, 2 sex treatments and 3 phases) and then were tested by DMRT. The results showed that the feed treatments (K, DJ, and P) significantly affected (P<0.05) the body weight (1583, 1289, and 1213 g), feed consumption (1180, 1051, and 1035 g), feed conversion (1.67; 2.62; and -1.89), percentage of abdominal fat (1.80, 2.03, and 1.29%). Sex (J and B) significantly influenced (P<0.05) on body weight, feed conversion, percentage of abdominal fat, but feed consumption, percentage of carcass, meat fat, had no significant differences. The interaction of sex and feed showed significant influence (P<0.05) on meat fat at 22 day of ages. The interaction of feed, sex, and phase had significant influence (P<0.05) on body weight and feed consumption. It could be concluded that stuff feeding decreased body weight, feed consumption, percentage of abdominal fat, but increased feed conversion and meat fat.(Key words: Broiler chicken, Sex, Feed stuff, Broiler Starter, Corn bran, Pollard)